Phosphorylation and cell adhesion properties of myelin-associated glycoprotein isoforms. - Afar, Daniel E. H. (University of Ottawa (Canada), 1992)
The phosphorylation and cell adhesion properties of myelin-associated glycoprotein (MAG) isoforms were investigated. MAG is a member of the immunoglobulin supergene family and is thought to mediate interactions between myelinating glial cells and neurons in the central and peripheral nervous systems. Two isoforms of MAG exist, L-MAG and S-MAG, which exhibit differential expression patterns. Using retroviral infection and transfection of the cDNAs encoding L-MAG and S-MAG, L cell fibroblasts and NIH3T3 cell lines that express either isoform were generated. The expression of both isoforms on the cell surface of L cells induced the cells to aggregate in a MAG-dependent fashion. The adhesion phenomenon was determined to be calcium and temperature independent. A critical level of cell surface MAG expression was required for cell aggregation to occur. The adhesion was found to be heterotypic in nature, signifying the presence of a MAG receptor on the cell surface of L cells. The MAG isoforms are identical in their extracellular and transmembrane domains. They share a common region in their cytoplasmic domain, but are distinct at their carboxyl termini. The unique carboxyl tails are comprised of 54 amino acids in L-MAG and 10 residues in S-MAG. Both isoforms were determined to be phosphorylated in fibroblasts. L-MAG exhibited phosphorylation on serine, threonine and tyrosine residues. The phosphorylation on tyrosine was augmented by treatment of cells with ammonium vanadate. S-MAG phosphorylation occurred mainly on serine residues, but some phosphotyrosine was also detected. The phosphorylation of S-MAG, however, was relatively insensitive to vanadate treatment. Tryptic digest analysis showed that two serine and the major tyrosine phosphorylation site in MAG were identical in L-MAG and S-MAG. The major tyrosine phosphorylation site in MAG was, thus, identified as tyrosine 558. This tyrosine residue is homologous to the major tyrosine phosphorylation site in the fibronectin receptor, integrin. A similar phosphorylation pattern of L-MAG was observed in primary rat oligodendrocytes. Determination of the stoichiometry of phosphorylation revealed that phosphorylation of L-MAG was at least one order of magnitude greater than S-MAG, especially with respect to tyrosine phosphorylation. This result indicates the presence of a carboxyl terminal sequence unique to L-MAG that activates the phosphorylation of tyrosine 558. This region may represent docking sites for protein tyrosine kinase binding, making L-MAG-kinase interactions more efficient. Two populations of L-MAG molecules were discovered: those that are phosphorylated on tyrosine residues, and those that exhibit serine/threonine phosphorylation. In effect, tyrosine phosphorylation precludes serine/threonine phosphorylation, suggesting that the alternatively phosphorylated L-MAG molecules perform different functions. Increasing the tyrosine phosphorylation of MAG had no detectable effect on the cell adhesion behaviour of the cells. Tyrosine phosphorylation of L-MAG, however, induced its capacity to bind the SH2 domain of phospholipase C-gamma. Therefore, L-MAG has the potential to interact with a variety of signalling molecules via its cytoplasmic domain. While L-MAG may participate in signal transduction pathways, S-MAG may function in a more restricted manner and perform only as a cell adhesion molecule. Thus, the differential regulation of MAG isoform expression may serve to increase the repertoire of MAG functions at specific times during development.
Keywords: Biology, Molecular.